Pemanfaatan Gerakan Salat Sebagai Upaya Mencegah dan Mengatasi Hipertensi - Oktafany; Rr Astri Nur Azizah Utama Utama; Rasmi Zakiah Oktarlina (Medula, 2022)
Hypertension is defined as systolic blood pressure> 140 mm Hg and diastolic blood pressure> 90 mm Hg. Hypertension is a major risk factor for cardiovascular disease and metabolic syndrome, which is influenced by aging, but hypertension is a preventable disease. One of the preventions of hypertension is lifestyle modification such as physical activity, diet, and emotional management. In another study also mentioned that the combination of physical activity and meditation has the same effectiveness in reducing and preventing increased blood pressure compared to only low-salt food diets. Salat is a kind of meditation that involves physical movements consisting of standing, bowing, prostration, and sitting. During salat, parasympathetic activity is increased which is marked by a decrease in heart rate, especially when the prostration position (69 bpm) and a decreased of systolic blood pressure by 2.5% and diastolic by 2.8%. It shows that salat has a positive effect on the cardiovascular system. Another study showed that salat also effects on musculoskeletal so salat can be used as physical therapy in geriatric rehabilitation. Study about the benefit of salat in the cardiovascular system is still limited, so further research is needed to prove the effectiveness of the use of salat as an alternative method in reducing the prevalence of hypertension in Indonesia.